The Effect of Service Quality on Customer Satisfaction Mediated by Brand Image and Customer Experience of Indibiz in Palu City - Sinta, Tri Ayu; Ponirin, Ponirin; Bachri, Syamsul; Auriza, Mohammad Zeylo (SIMAK, 2025)
This study aims to analyze the influence of service quality on customer satisfaction mediated by brand image and customer experience of Indibiz n Palu City. This research employs a quantitative method. The population of the study consists of Indibiz customers at PT Telkom Witel Sulbagteng in Palu City, with a sample size of 105 respondents. Data collection was conducted using a Google Forms questionnaire, and the sampling technique applied was purposive sampling. The data analysis technique used in this study is Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the assistance of SMARTPLS software. The results indicate that the brand image variable does not significantly affect customer satisfaction, while service quality has a significant impact on customer satisfaction, and customer experience also has a significant impact on customer satisfaction. The quality of service mediated by brand image does not have a significant effect on customer satisfaction. The quality of service mediated by customer experience has a significant effect on customer satisfaction.